Fat history : bodies and beauty in the modern West - Stearns, Peter N. (UPCC book collections on Project MUSE., 1997)
The modern struggle against fat cuts deeply and pervasively into American culture, as evidenced by the compulsion to stay thin, or at least to profess a desire to become thin. Dieting, weight consciousness, and widespread hostility to obesity form one of the fundamental themes of modern life in countries like the United States and France. Interestingly, while the French are renowned for their delight in all things gustatory, they are significantly trimmer and less diet obsessed than Americans.